The Role of Strategic Insight Requirements in Achieving Organizational Excellence: A Survey Study of the Opinions of a Sample of Heads of Scientific Departments in a Number of Government Universities / Kurdistan Region of Iraq - محمد علي, نزار; خليل إسماعيل, هادي; شريف يوسف, ميهفان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The purpose: The aim of the current study is to diagnose the role of strategic foresight requirements (strategic awareness, strategic dialogue, business intelligence, and capacity integration) in achieving organizational superiority (strategic planning, focus on operations, focus on workforce, information and analysis)، and an analysis of the relationship between them in public universities / Kurdistan Region. The study problem: The problem of the study is the need for public universities to achieve organizational superiority. The problem of the study was expressed through a number of questions, including what is the degree of adoption of strategic foresight requirements? What is the level of organizational superiority achieved by the surveyed universities? Is there a significant impact of strategic foresight requirements in achieving organizational superiority? Design / methodology: To achieve the objective of the study, the analytical descriptive approach was used to collect and analyze data to reach the results, and a questionnaire was adopted to collect data, and the final number of respondents reached (340) from the heads of scientific departments in all 14 public universities in the Kurdistan Region. The hypotheses were tested by adopting a number of statistical methods using the statistical package (SPSS version24). Conclusions and Suggestions: The study came out with a set of conclusions by presenting the results of testing and analyzing the hypotheses of the study, the most important of which is the presence of a significant impact of strategic foresight requirements in achieving organizational superiority at the level of the overall indicator and at the level of dimensions, which means that whenever the surveyed universities adopt the requirements of strategic foresight, this leads to increase the ability of these universities to achieve organizational superiority.Based on the conclusions, a number of suggesions were presented, the most important of which is that it is necessary for the surveyed universities to adopt the requirements of strategic foresight and apply them in reality, as they effectively contribute to achieving the organizational superiority of these universities and adapting to environmental pressures and variables. Originality / Value: The originality of the study stems from the scarcity of field studies that dealt with the relationship between strategic foresight requirements and organizational superiority in the environment of the Kurdistan Region, which means that there is a knowledge gap that highlights the need to bridge this gap through field studies in order to reach a better understanding of the nature of the relationship between them.